The Effect of the Internet on Performance and Quality: Evidence from the Airline Industry - Ater, Itai; Orlov, Eugene (The Review of Economics and Statistics, 2015)
We argue that the rise of online travel agencies changed the nature of competition in the airline industry—from competition on elapsed scheduled flight times to price competition. Using flight-level data between 1997 and 2007 and geographical Internet growth patterns, we find a positive relationship between Internet access and flight times. The magnitude of this relationship is larger in competitive markets without low-cost carriers and for flights with shortest scheduled times. We also find that flight delays increased as more passengers gained Internet access. These findings suggest that the Internet may adversely affect firms’ performance and incentives to provide high-quality products.